ANALISIS PENGEMBANGAN E-GOVERNMENT DI KOTA SEMARANG (STUDI WEBSITE RESMI KOTA SEMARANG) - Prasetyo, Alfian Adi; Nurcahyanto, Herbasuki; Rihandoyo, Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The development of e-government in Semarang is one of the programs implemented by the government of Semarang to ease the service towards substantial stakeholders, such as the public society and private sectors by using information technology advances. Result of observations and interviews with several informants indicate . The development of e-government in the city of Semarang is inhibited by a variety of factors such as lack of available resources, infrastructure, and government commitment.